Infix -UM- as Verbal Former in Muna Language: Morphology, Semantic, and Syntax Analysis - La Ode Nggawu (Bandar Lampung University (UBL), 2013)
This paper is concerned with study of infix -um- in Muna language as verbal former. The using of Muna language found mostly in Muna regency and a part of Buton and Kendari regencies of Southeast Sulawesi. The objectives of the study are to describe the morphology system, the function and the meaning, and the syntax aspects of infix -um- in Muna language. The data of this study come from some informants and the writeras native speakers of Muna languages. The data which have been collected through noting and recording weretabulated and analyzed by using morphological, semantic, and syntactical analysis in descriptive qualitatively method. Further, it uses [20] of morphology and semantics, and[10] of transitive and intransitive verbs (syntaxes). Based on the writer interpretation, the result of the study shows that (1) infix -um- has four allomorphs are /-um-/, /-im-/, /m-/, and /ø/, (2) the use of each allomorph depends on the initial and the second phonemesof certain base verbal word, (3) infix -um- has inflective function which means ‘will’, and (4) infix -um- with all allomorph forms can be inserted or infixed both in transitive and intransitive verbs.